2019
DOI: 10.1016/j.cmi.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

‘A five-day course of oral antibiotics followed by faecal transplantation to eradicate carriage of multidrug-resistant Enterobacteriaceae’ – Author's reply

Abstract: We would like to thank Mullish et al. for their letter regarding our study [1,2]. They rightly point out that the amount of faecal material (15e30 g of stool) used in patients treated with capsulized faecal microbiota transplant (FMT) was low and below the minimum of 30 g recommended in the 2017 European Consensus Conference on Faecal Microbiota Transplantation in Clinical Practicefor the treatment of recurrent Clostridium difficile infection (CDI) [3]. At the time when the trial was planned (September 2012) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 4 publications
1
18
0
1
Order By: Relevance
“…Four studies investigated the effects of FMT capsules to treat or eradicate multidrug-resistant bacteria or recurrent infections. 5760 In a multicentre RCT, Huttner and colleagues 59 treated carriers of multidrug-resistant Enterobacteriaceae with 2 days of FMT capsules preceded by 5 days of antibiotics. Seven of the sixteen FMT-treated patients were decolonised from extended spectrum beta-lactamase Enterobacteriaceae (ESBL-E) or carbapenemase-producing Enterobacteriaceae (CPE) as opposed to 3 of 13 in the placebo group that did not receive any treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies investigated the effects of FMT capsules to treat or eradicate multidrug-resistant bacteria or recurrent infections. 5760 In a multicentre RCT, Huttner and colleagues 59 treated carriers of multidrug-resistant Enterobacteriaceae with 2 days of FMT capsules preceded by 5 days of antibiotics. Seven of the sixteen FMT-treated patients were decolonised from extended spectrum beta-lactamase Enterobacteriaceae (ESBL-E) or carbapenemase-producing Enterobacteriaceae (CPE) as opposed to 3 of 13 in the placebo group that did not receive any treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently suggested that CD patients with a low microbial load presented a better response to FMT ( Sarrabayrouse et al, 2020 ). Moreover, oral decontamination with antibiotics such as colistin or aminoglycosides has been proposed to enhance the efficacy of FMT ( Huttner et al, 2019 ; Saidani et al, 2019 ). Thus, an initial low microbial load or reducing the microbial load in UC patients may promote the colonization of donor microbiota thereby enhancing the efficacy of FMT.…”
Section: Discussionmentioning
confidence: 99%
“…Stool sample(s) collected from a healthy volunteer were prepared based on the protocol described in Youngster et al (2014) andused in a large randomized controlled trial (Clinicaltrials.gov, NCT02472600) (Huttner et al, 2019). Briefly, fresh stool was suspended in NaCl 0.9% (6 mL per g of stool) using a commercial blender and sequentially sieved using 1, 0.5, and 0.25-mm Nylon filters (NITEX, Milian).…”
Section: Samples Handling and Dna Extractionmentioning
confidence: 99%